A Toddler With Prolonged Fever and Intermittent Cough - Carson Gill MD, MSc; Ori Scott MD; Carolyn E. Beck MD, MSc, FRCPC (SAGE Publishing, 2019)
Fever of unknown origin is an important diagnostic challenge in pediatrics that requires a thoughtful approach. The differential diagnosis is broad and includes infectious, autoimmune, oncologic, neurologic, genetic, and iatrogenic causes. Infection remains the most common etiology, and uncommon presentations of infections are still more likely than classic presentations of rare conditions. We report a case of a retropharyngeal abscess in a toddler whose presentation is marked by a prolonged fever (>3 weeks). This case highlights the importance of close follow-up with serially repeated history and physical examinations to guide the evaluation of a patient with fever of unknown origin.